UPAYA MENINGKATKAN HASIL BELAJAR PPKn DENGAN MENGGUNAKAN PEMBELAJARAN KOOPERATIF MODEL ROUND TABLE DAN PROBLEM POSING KELAS X MIPA 3 SEMESTER GENAP SMA NEGERI 1 KERAMBITAN TAHUN PELAJARAN 2016/2017 - Wiryana, I Dewa Ketut (LP2M IKIP PGRI Bali, 2018)
The aim of this research is to know the impact of application of cooperative model table round and of problem posing to improving students? achievement. This reascarch is classroom action research and it is planned in 2 cycle, every cycle involve 4 steps i.e, plan phase,action phase, observation phase, and phase of reflection. This Research Subyek is all of student of X MIPA 3 SMA Negeri 1 Kerambitan. Data was collected by tes, observation, field note, and documentation method. Pursuant to result of this research, usage of model of round and table of problem posing can improve result learn class student of X MIPA 3 SMA Negeri 1 Kerambitan.